Structuring International Cooperative Ventures - Noe, Thomas H.; Rebello, Michael J.; Shrikhande, Milind M. (Review of Financial Studies, 2002)
We examine the effect of bargaining power and informational asymmetry on the design of international cooperative ventures in the presence of restrictions on equity participation and investment. When the bargaining advantage rests with the multinational, equity participation restrictions can increase the profits to domestic firms and encourage suboptimal investment policies. Overinvestment occurs when the multinational's bargaining advantage is reinforced by an informational advantage, while underinvestment occurs when the domestic firm possesses the informational advantage. In contrast, when the bargaining advantage rests with the domestic firm, equity participation restrictions do not affect investment levels. Copyright 2002, Oxford University Press.